Influencing Factors and Prevalence of Anxiety in Medical Students: A Cross-Sectional Study - Nguyen, Huong Thi; Phan, Yen Thi Hoai; Nguyen-Hoang, Anh-Vu; Nguyen, Tri-Bao; Tran-Thien, Gia-Phuoc (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: While current research highlights student anxiety globally, limited data exists on the specific situation of Vietnamese medical students. This study addresses this gap by investigating the prevalence and contributing factors of anxiety within this population, aiming to gain a deeper understanding of their mental health experiences. Methods: Utilizing a convenience sampling technique, 400 medical students from Ho Chi Minh City University of Medicine & Pharmacy were surveyed using the Zung Self-Rating Anxiety Scale and a custom questionnaire assessing factors contributing to anxiety. Data analysis included descriptive statistics, independent-samples t-tests, ANOVA, and Pearson's correlation. Results: Findings revealed mild to moderate anxiety levels among medical students (M = 49.68 ± 11.54), with significant differences based on gender, academic year, and academic performance. Males (M = 51.27 ± 12.26) and senior students (M = 53.18 ± 12.50) reported higher anxiety levels. Key contributors to anxiety included financial concerns, major examinations, and discrepancies between perceived and desired academic performance. Notably, a strong positive correlation was found between academic performance discrepancies and anxiety levels (r = 0.888, p < 0.001). Conclusion: The study highlights a potentially higher prevalence of anxiety among medical students than previously reported, emphasizing the need for targeted interventions. Understanding the multifaceted nature of anxiety and its contributing factors is crucial for fostering a supportive learning environment, ultimately nurturing well-equipped and resilient healthcare professionals.